Best practices for monitoring and risk control in social projects: a review - Gomes, Keydson Quaresma; Eiras, Katia Maria Morais; Pozo, Osmar Vicente Chevez (Brazilian Journal of Production Engineering, 2026)
projects, and therefore, this study aimed to identify the best practices for risk monitoring and control (RMC) in social projects. A literature review was conducted to identify the practices that represent the pillars of social risk management. The search was carried out in the databases Web of Science, Scopus, and Google Scholar. After applying filtering methods, 41 articles were selected to identify the terms corresponding to RMC practices. The review highlighted that social risk is associated with the occurrence of uncertain consequences (positive or negative) arising from planned actions or events that impact social relationships and collective values, creating instability, conflicts, or vulnerabilities. The study provided a comparison between the management of a traditional project and a social project. The eight best practices for risk monitoring and control in social projects were identified, with those found most frequently in the reviewed literature being highlighted. The conclusion of this work aimed to show that this approach represents a significant academic contribution, providing a more coherent and accessible perspective on the best practices for risk monitoring and control in social projects.